Effectiveness of metronidazole in the treatment of tumor wound odors - Barreto, Arthur Monte (2018)
Objective: to analyze the evidence of the effectiveness of Metronidazole in the treatment of odors in tumor wounds. Methods: this is an integrative review performed at the health databases and the PubMed portal. The studies were evaluated by the Jadad Scale (randomized clinical trials), Downs and Black (quasi-experiment) and the Strengthening the Reporting of Observational studies in Epidemiology (observational). A sample of the ten studies and articles were considered cut-off points that reached 50.0% of the criteria. Results: Metronidazole was effective in 95.6% of the cases and the gel preparation at 0.75% was the most used in the studies. Conclusion: the evidence indicates that metronidazole is safe and effective in the control of tumor wound odors, but there is no consensus on the most effective forms of presentation and administration routes. Most studies associate the appearance of bad odor with the growth of anaerobic bacteria in the tumor tissue.